2019
DOI: 10.1080/09540105.2018.1548578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dandelion root extract on growth performance, immune function and bacterial community in weaned pigs

Abstract: This study was conducted to evaluate the effect of dietary Chinese herb medicine extracted from Dandelion root on growth performance, serum immune markers, faecal bacterial community and their metabolites in weaned pigs. The results showed that dietary Dandelion root extract (CHE) supplementation decreased (P < .05) the diarrhoea frequency, but had no effect on growth performance of weaned pigs. Dietary CHE supplementation increased (P < .05) propionate and butyrate concentrations in faecal samples of pigs. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…(2013) , who demonstrated that dietary supplementation with A. vera polysaccharide increased IFN-γ production in serum of weaned piglets. Furthermore, some others had also reported that dandelion root extract (major bioactive components are polysaccharide and flavone) and Astragalus polysaccharide supplementation in the diet increased IFN-γ level in serum of pigs ( Yuan et al., 2006 , Zhao et al., 2019 ). Therefore, these results implies that dietary supplementation with certain kinds of Chinese herbs could improve the immune function of weaned pigs.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) , who demonstrated that dietary supplementation with A. vera polysaccharide increased IFN-γ production in serum of weaned piglets. Furthermore, some others had also reported that dandelion root extract (major bioactive components are polysaccharide and flavone) and Astragalus polysaccharide supplementation in the diet increased IFN-γ level in serum of pigs ( Yuan et al., 2006 , Zhao et al., 2019 ). Therefore, these results implies that dietary supplementation with certain kinds of Chinese herbs could improve the immune function of weaned pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, preparations exerting both antioxidant and anticoagulant activities based on safe natural substances are continuously sought after for their potentially wide range of health benefits in the prevention and treatment of cardiovascular disorders [1][2][3][4][5][6][7].Nowadays, the dandelion (Taraxacum officinale) herb and root are used as a component of food products, dietary supplements and pharmacological preparations for various ailments (mainly liver, gallbladder and kidney disorders) [8,9]. This is due to a wide range of biological activities, including antihyperglycemic, antioxidant and anti-inflammatory actions demonstrated by dandelion fractions and their constituents, with no reported adverse effects, together with a well-understood chemical composition and a widespread occurrence of the plant throughout the world [10,11]. Aqueous-organic extracts from the dandelion herb were found to exert an anti-inflammatory action [12], mainly due to decreasing the expression of proinflammatory cytokines by inhibiting the nuclear factor (NF)-κB [13], tumor necrosis factor (TNF)-α and interleukin (IL)-1β [14], as well as reducing the expression and production of inducible nitric oxide synthase/nitric oxide (iNOS/NO) and cyclooxygenase (COX)-2/prostaglandin E2 [15].Plant polyphenols have the ability to protect dietary lipids, proteins and vitamins from oxidation.…”
mentioning
confidence: 99%
“…Herb complex extract also has been widely used as a substitute for antibiotics in feed additives (Yan, Meng, & Kim, 2012;Zhou, Zhang, & Kim, 2013). It also confirmed that the addition of herbal extracts to diets could improve the growth performance and immune function of weaned piglets (Zhao, Zhang, Zhou, Dong, & Zhang, 2019). Multi-enzyme complex also can promote the digestion and absorption of nutrients and, effectively inhibit the growth of pathogenic bacteria in the intestinal tract of livestock and poultry (Mohammadi Gheisar, Hosseindoust, & Kim, 2016;Zhang, Yang, Wang, Yang, & Zhou, 2014).…”
Section: Introductionmentioning
confidence: 81%